Anak Dalam Perspektif Hadis - Suryadi, Suryadi (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
The future of a nation, including Indonesia, can be predicted from the current condition of its children. A nation may have a good vision of their future if children are living in a good life, in a good health whether physically or psychologically, and free from any violence. In contrast, if the current condition of children is bad, such as what we find in Indonesia which is among the eight most populous Muslim countries, we may be pesimistics over the future of our nation. Children experiencing violences one after another particularly in Muslim counries intrigues our conscience whether there is something wrong in our understanding over religious texts, hadits in this context. Hadits has been taken as a religious source for raising children, for education as well as development of children's future. Presumably incorrect understanding of hadits on children raising and education has provoked violence on them. This article seeks to present better understanding of several prophetic traditions on children issues, and to promote the messages of the Prophet Muhammad to rectify the quality of children.